2003
DOI: 10.1590/s0066-782x2003000400001
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities in neurological diseases

Abstract: Original ArticleCentral nervous system disorders are known to be responsible for the onset of cardiac alterations, frequently observed in the electrocardiogram 1,2 . Although serum potassium disturbance has been suggested as an important factor in these alterations, this finding was not confirmed in several studies 3,4 . The majority of studies suggest that these ECG abnormalities result from disturbances in the autonomous system, due to neurologic disease, promoting a local excess of catecholamines, associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…EKG abnormalities occur in 25–75% of SAH patients while arrhythmias were recorded in all of them. Furthermore, ST elevation in 3% of the patients with intracranial tumors was also described [11]. According to the NSC definition, we observed very high troponin I and BNP levels in our patients and significant changes in EKG and transesophageal echocardiogram for cardiac injury as well as hemodynamic parameter abnormalities.…”
Section: Discussionsupporting
confidence: 62%
“…EKG abnormalities occur in 25–75% of SAH patients while arrhythmias were recorded in all of them. Furthermore, ST elevation in 3% of the patients with intracranial tumors was also described [11]. According to the NSC definition, we observed very high troponin I and BNP levels in our patients and significant changes in EKG and transesophageal echocardiogram for cardiac injury as well as hemodynamic parameter abnormalities.…”
Section: Discussionsupporting
confidence: 62%
“…[7,8] Other studies have reported incidence of sinus bradycardia in 4-12% of patients with brain tumors. [17][18][19] In our study, the repolarization abnormalities, that is, ST-segment depression, ST elevation, and T-wave changes, were found in 12, 16, and 16%, respectively, of Group 2 patients. e cellular mechanism for the repolarization changes in acute neurological conditions has been attributed to the sympathetic hyperactivity and the resultant release of large volumes of norepinephrine from the sympathetic nerve terminals.…”
Section: Discussionsupporting
confidence: 49%
“…Abnormalities associated with ischemia, such as ST-segment changes, T-wave inversions, and arrhythmias were observed only in a few cases. [28][29][30] In our study, 72.4% of the ECG's were abnormal. Patients with SDH were the only ones with Q waves or left axis deviation or bundle branch blocks )3% and 21.2%, respectively(.…”
Section: Discussionmentioning
confidence: 87%